Offline drone instrumentalized ambulance for emergency situations - Mohapatra, Hitesh (IAES International Journal of Robotics and Automation (IJRA), 2020)
In this paper, an offline drone instrumentalized ambulance (ODIA) mechanism has been discussed. The rapid increase in the urban population directly influences every sector of society. The sectors are maybe food, health care, education, transportation, etc. Normally, it has been observed that when any accidents happen on the urban road or any remote places then, the availability of immediate medical help is very rare. It is not because of the unaware or unavailability of medical facilities rather it happens because of overcrowding on the urban road and geographical odd-isolation of places. Hence, here an ODIA concept has been discussed which uses offline maps and offline first-aid medical videos through which immediate medical help can be made available at the patient end. This model helps to save the life of an accident victim by providing immediate medical attention. The key strength of ODIA is, it is independent of internet service that is why it is more suitable for harsh and hostile environments.